: № 160 (2080) (1983)
Титульного листа нет, описание составлено по обложке Для служебного пользования, экз. № 96 Экземпляры: УКП (20240814) / Инвентарный номер: АП19830206 / Сис.шифр: 65.31 / Авт.знак: И 93 / ГРНТИ: 06.35.33 / ББК: 65.31-05